Skin microbiome influences the progression of cutaneous squamous cell carcinoma through the immune system - Zijian Zhang; Lili Liang; Xiaoke Jiang; Jixuan Shan; Siying Li; Jie Liu; Qinyi Dong; Xinman Wang; Han Zhang (World Journal of Surgical Oncology)
Abstract Cutaneous squamous cell carcinoma (cSCC) is a type of skin tumor that develops in the epithelial cells. This disease has the second highest incidence of human skin cancers, with a high metastatic rate. While ultraviolet radiation significantly contributes to the genomic changes that support cSCC development, the dysbiosis of the skin microbiome and influence of the immune system also play important roles in this process. In this review, we discuss the effects of skin microbes and their metabolites on the immune system, including innate immune cells, T cells, and cytokines. We also discuss how Staphylococcus aureus and human papillomavirus can affect cSCC by impacting the immune system. Furthermore, we explore the antagonism of symbiotic microorganisms with cSCC-associated pathogens and their potential as novel therapeutic modalities.